Production and Nitrogen Use Efficiency of Oat Forages Receiving Slurry or Urea. (1st July 2016) - Coblentz, Wayne; Jokela, William; Cavadini, Jason S.
Abstract : Although fall‐grown oat ( Avena sativa L.) has potential for use as supplementary fall forage throughout the north‐central United States, one additional benefit is the option for summer manure distribution that is not possible within a conventional corn ( Zea mays L.) cropping program. 'ForagePlus' oat was seeded into replicated plots fertilized with urea at rates of 0, 20, 40, 60, or 100 kg N ha −1 or with dairy slurry applied at approximately 42, 300 and 84, 600 L ha −1 (105 and 209 kg N ha −1, respectively). Apparent N recovery from fall‐grown oat plots fertilized with urea ranged from 65.8 to 89.8%. This suggested aggressive scavenging of N, but calculation of these high apparent N recovery rates was dependent on relatively low preplanting soil NO3 –N concentrations, as well as a good dry matter (DM) yield response to N fertilization ( y = −0.114 x 2 + 29.9 x + 2130; R 2 = 0.982). For this study, applications of high and low rates of dairy slurry yielded respective N fertilizer equivalencies of 38 and 45 kg N ha −1 for fall‐grown oat, which are roughly equivalent to Wisconsin recommendations for cereal grains (45 kg N ha −1 ). Apparent N recovery following application of the high and low rates of dairy slurry was 18.1 and 25.5%, respectively; however, when expressed on the basis of NH4 –N applied, apparent N recovery for fall‐grown oat averaged 53.5% and did not differ among slurry application rate treatments. Fall‐grown oat appears to be an effective scavenger of N applied as NH4 –N from dairy slurry. Core Ideas Fall‐grown oat possesses unique forage quality characteristics. Fall‐grown oat can serve as attractive emergency fall forage. Use of fall‐grown oat allows for summer manure application that is decoupled from corn production. Fall‐grown oat is an effective scavenger of NH4–N applied from dairy slurry. Fall‐grown oat may be a useful tool in managing N from dairy manures.